Six -Legs Walking Robot - Lim, Siew Lay (UTeM, 2008)
The six-legs walking robot can walk on 6 legs. This robot uses the infrared sensor to explore the environment and avoid from obstacles. It has the ability to turn and reverse, walk on rough ground and avoid obstacles. All the robot's functions are controlled by a Microchip PIC 16F84A micro controller. The objective of this project is to solve the instability problem using tripod gait as control algorithm. Besides, infrared sensor is also used to overcome the obstacles problem. Insectronic in history face the problem of stability in walking movement. When a walking robot traverses ground that not smooth, several control problems may arise from it. The problems include navigation where the robot must choose a route that will get it to a specified location. The second problem is with path selection that the robot must choose the detail of route to minimize the problem of slope roughness and obstacles avoidance if a specified location is given. The third problem is with terrain adaptation and obstacle crossing. With the completion of this project, the robot equips by the three servos and a main controller board has the ability to walk forward and backward, walk on rough ground and reacts to its environment. The robot will also possess obstacles-avoidance capabilities to the front and on both sides of its head that necessary for survival by an infrared sensor board.